Extent of Knowledge of ATMA Beneficiaries and Non-beneficiaries Farmers towards Improved Wheat Cultivation Technology (Indian Journal of Extension Education, 2016)
The study was conducted in Arazilines and Kashividyapeeth block of Varanasi distract of Uttar Pradesh to identify the impact of ATMAtraining programme on extent of knowledge about improved wheat cultivation technologies. 120 trained and 120 untrained farmers were selected trough PPS technique for study. 60.83 per cent trained farmers were in medium knowledge level regarding improved wheat cultivation technologies. Besides 20.83 per cent and 18.33 per cent untrained farmers were in low and high knowledge level respectively. While in case of untrained farmers 70.83 per cent were in medium knowledge level regarding improved wheat cultivation technologies. Besides 20.83 per cent and 8.33 per cent untrained farmers were in low and high knowledge level respectively. The study revealed that trained farmers had higher extent of knowledge of about improved wheat cultivation technologies than untrained farmers.